Me and my smartphone. Motivations for using it among young Chileans. A study over time - Leiva Soto, Ricardo Alberto (2024)
The objective of our research is to measure how uses and motivations to use smartphones by young Chilean populations have changed through time and how these motivations to engage with smartphones affect the time spent texting on these portable devices. We replicated a face-to-face survey between Chilean millennials and centennials, firstly conducted in 2009 (n= 1,320), repeated in 2015 (n= 744), and conducted again in 2021 (n= 846). This last wave was conducted between July and November to subjects aged 18-25 living in Chile. The questionnaire included 44 questions based on scales previously validated in studies relating the Uses and Gratifications Theory with mobile phones, attitudes towards technology, and evaluations of users about mobile phones’ attributes defined by Albarran (2009). There were also variables related to demographic data (i.e., area of residence) and gender, which respondents declared. Most motivations to use smartphones measured in our survey of 2021 were the same as we measured in 2015 and 2009, but others are new. To measure how the appeal of motivations changed over time, we conducted a comparison of means. We also ran an exploratory factor analysis to aggregate motivations and regression analyses to quantify how motivations affected youths’ texting time.